A Review of Pharmacologic Treatment for Compulsive Buying Disorder - Soares, Célia (2016)
At present, no treatment recommendations can be made for compulsive buying disorder. Recent studies have found evidence for the efficacy of psychotherapeutic options, but less is known regarding the best pharmacologic treatment. The purpose of this review is to present and analyze the available published evidence on the pharmacological treatment of compulsive buying disorder. To achieve this, we conducted a review of studies focusing on the pharmacological treatment of compulsive buying by searching the PubMed/MEDLINE database. Selection criteria were applied, and 21 studies were identified. Pharmacological classes reported included antidepressants, mood stabilizers, opioid antagonists, second-generation antipsychotics, and N-methyl-D-aspartate receptor antagonists. We found only placebo-controlled trials for fluvoxamine; none showed effectiveness against placebo. Three open-label trials reported clinical improvement with citalopram; one was followed by a double-blind discontinuation. Escitalopram was effective in an open-label trial but did not show efficacy in the double-blind phase. Memantine was identified as effective in a pilot open-label study. Fluoxetine, bupropion, nortriptyline, clomipramine, topiramate and naltrexone were only reported to be effective in clinical cases. According to the available literature, there is no evidence to propose a specific pharmacologic agent for compulsive buying disorder. Future research is required for a better understanding of both pathogenesis and treatment of this disorder.